A Retrospective Analysis of the Safety and Activity of Lutetium‐177‐Prostate‐Specific Membrane Antigen Radionuclide Treatment in Older Patients with Metastatic Castration‐Resistant Prostate Cancer. (10th June 2020) - Leibowitz, Raya; Davidson, Tima; Gadot, Moran; Aharon, Margalit; Malki, Avraham; Levartovsky, Meital; Oedegaard, Cecilie; Saad, Akram; Sandler, Israel; Ben‐Haim, Simona; Domachevsky, Liran; Berger, Raanan
Abstract: Background: Prostate cancer is a common malignancy of the elderly, and with the aging of the population, the need is growing for therapies suitable for this age group. Lutetium‐177–prostate‐specific membrane antigen (Lu‐PSMA), a radiolabeled small molecule, binds with high affinity to prostate‐specific membrane antigen, enabling beta particle therapy targeted to metastatic castration‐resistant prostate cancer (mCRPC). In a recent single‐arm phase II trial and a subsequent expansion cohort, a prostate‐specific antigen (PSA) decline of ≥50% was observed in approximately 60% of patients receiving Lu‐PSMA. Taking into account the specific challenges and potential toxicities of Lu‐PSMA administration in elderly men, we sought to retrospectively analyze the safety and activity of Lu‐PSMA in men aged older than 75 years with mCRPC. Patients and Methods: The electronic medical records of 24 patients aged older than 75 years treated with Lu‐PSMA "off‐trial" were reviewed, and clinical data were extracted. Clinical endpoints were toxicity and activity, defined as a PSA decline ≥50%. Descriptive statistics were performed using Excel. Results: The median age at treatment start was 81.7 years (range 75.1–91.9). The median number of previous treatment lines was four. The number of treatment cycles ranged from one to four; the mean administered radioactivity was 6 GBq per cycle. Treatment was generally tolerable; side effects included fatigue ( n = 8, 33%), anemia ( n = 7, 29%), thrombocytopenia ( n = 5, 21%), and anorexia/nausea ( n = 3, 13%). Clinical benefit was observed in 12 of 22 patients (54%); PSA decline above 50% was observed in 11 patients (48%) and was associated with significantly longer overall survival. Conclusion: Our results indicate that Lu‐PSMA is safe and active in elderly patients with mCRPC. Implications for Practice: Lutetium‐177–prostate‐specific membrane antigen (Lu‐PSMA), a radiolabeled small molecule, binds with high affinity to prostate‐specific membrane antigen, enabling beta particle therapy targeted to metastatic castration‐resistant prostate cancer (mCRPC). The recently published single‐arm phase II trial with Lu‐PSMA, describing its safety and activity, did not include patients aged older than 75 years. In this study, Lu‐PSMA activity was retrospectively analyzed in patients aged older than 75 years and results indicate that treatment was tolerable and similarly active in this age group, with no new emerging safety signals. Despite the small cohort size, this analysis suggests that Lu‐PSMA can serve as an advanced palliative treatment line in mCRPC in elderly patients. Abstract : With the aging population, the need for therapies for prostate cancer in the elderly is growing. This article provides a retrospective analysis of the safety and activity of Lutetium‐177 prostate‐specific membrane antigen (Lu‐PSMA) in men older than 75 years treated at a single institution.